Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1021/acsabm.2c00820
|View full text |Cite
|
Sign up to set email alerts
|

Serum Albumin Inspired Self-Assembly/Disassembly of a Fluorogenic Nanoprobe for Real-Time Monitoring and Quantification of Urinary Albumin with Live Cell Imaging Application

Abstract: Abnormal levels (high/low) of urinary human serum albumin (HSA) are associated with a number of diseases and thus act as an essential biomarker for quick therapeutic monitoring and biomedical diagnosis, entailing the urgent development of an effective chemosensor to quantify the albumin levels. Herein, we have rationally designed and developed a small fluorogenic molecular probe, (Z)-2-(5-((8-hydroxy-2,3,6,7-tetrahydro-1H,5H-pyrido[3,2,1-ij]quinolin-9-yl) methylene)-4-oxo-2-thioxothiazolidin-3-yl) acetic acid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 68 publications
0
7
0
Order By: Relevance
“…which can lead to cardiovascular and renal damage. 66,67 The LOD values obtained for the four BODIPY derivatives show their efficacy as good serum protein indicators.…”
Section: Resultsmentioning
confidence: 89%
“…which can lead to cardiovascular and renal damage. 66,67 The LOD values obtained for the four BODIPY derivatives show their efficacy as good serum protein indicators.…”
Section: Resultsmentioning
confidence: 89%
“…From this fluorescence titration study, we have calculated the dissociation constant ( K d ) between DBNHC and BSA by utilising the following equation: 40 …”
Section: Resultsmentioning
confidence: 99%
“…36,37 Recently, it has been shown that self-assembly based nanoprobes have displayed some distinct advantages for protein sensing because of their high photostability, biocompatibility, flexibility in chemical design and fine-tuning of optical properties. [38][39][40] For instance, a selfassembled probe exhibits no or very weak fluorescence due to the aggregation caused quenching (ACQ) effect, but when the probe responds to the target analytes by undergoing disassembly, it will emit strong fluorescence. 41 However, a very few number of fluorescent probes have been reported for detection of proteins in virtue of different strategies including polymer nanoparticles 38,42 or affinity ligand-based aggregate disassembly 40,[43][44][45] and metal nanoparticle displacement.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations